National cross-sectional survey on psychological impact on French nursing homes of the first lockdown during the COVID-19 pandemic as observed by psychologists, psychomotor, and occupational therapists - Vaillant-Ciszewicz, Anne-Julie; Couturier, Bérengère; Segaux, Lauriane; Canouï-Poitrine, Florence; Guérin, Olivier; Bonin-Guillaume, Sylvie (Frontiers in Public Health, 2023)
Objectives The main objective was to explore the psychological impact of the French lockdown during the first wave of the COVID-19 pandemic on nursing home residents, their relatives, and healthcare teams, as observed by mental health professionals. Design A national online cross-sectional survey was conducted from May 11 to June 9, 2020. Setting and participants Respondents were psychologists, psychomotor therapists, and occupational therapists (mental health professionals). Results A total of 1,062 participants responded to the survey, encompassing 59.8% psychologists, 29.2% occupational therapists, and 11% psychomotor therapists. All mental health professionals felt fear (76.1%), fatigue and exhaustion (84.5%), and inability to manage the emotional burden (78.4%). In nursing homes with COVID-19 cases, residents felt significantly sadder (83.2%), more anxious (65.0%), experienced more anorexia (53.6%), resurgence of traumatic war memories (40.2%), and were more often disoriented (75.7%). The suffering of relatives did not vary between nursing homes with and without COVID-19 cases. The nursing staff was heavily impacted emotionally and was in need of psychological support particularly when working in nursing homes in a low COVID-19 spread zone with COVID-19 cases (41.8 vs. 34.6%). Conclusion and implications Primary prevention must be implemented to limit the psychological consequences in the event of a new crisis and to prevent the risk of psychological decompensation of residents and teams in nursing homes.